2009
DOI: 10.1007/s10643-009-0304-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Children’s Literature to Teach Standard-Based Science Concepts in Early Years

Abstract: This paper discusses the benefits and limitations of using children's literature in introducing science concepts to young children. The manuscript also provides an overview of preschool science standards of 12 states and presents lists of appropriate children's literature suitable to use in teaching science concepts targeted in those preschool science standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 18 publications
2
60
0
6
Order By: Relevance
“…Good science education is essential in early childhood, not only for social and cognitive development but also for engaging young (3-5 years old) learners with science (Sackes et al, 2009). However, science is often perceived as unappealing to young learners (Koren and Bar, 2009;Sjøberg and Schreiner, 2005;Stefansson, 2006;Muller et al, 2013).…”
Section: A Pedagogic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Good science education is essential in early childhood, not only for social and cognitive development but also for engaging young (3-5 years old) learners with science (Sackes et al, 2009). However, science is often perceived as unappealing to young learners (Koren and Bar, 2009;Sjøberg and Schreiner, 2005;Stefansson, 2006;Muller et al, 2013).…”
Section: A Pedagogic Perspectivementioning
confidence: 99%
“…However, many teachers find science challenging to teach and, as such, turn to picture books and children's science literature for assistance. Sackes et al (2009) explored the benefits and limitations of using children's literature to introduce science concepts. The authors found that although some books are poorly written and can spread misconception, those written under the guidance of science consultants were great learning tools, offering unique opportunities for introducing science concepts in the early years, fostering interest, curiosity, and positive attitudes, as well as integrating literacy and science (Broemmel and Rearden, 2006;Castle and Needham, 2007;Coskie, 2006;Monhardt and Monhardt, 2006).…”
Section: A Gires Et Al: Making Rainfall Features Fun: Scientific Acmentioning
confidence: 99%
“…Westin (2003 a,b) has studied technology and cyborgs in Astrid Lindgren's books about Karlsson on the roof. In the field of science and technology education more broadly defined there are some studies that address children's literature in education such as Sackes et al (2009) andSchroeder et al (2009), which deal with possibilities and obstacles in using children's fiction books in the science classroom.…”
Section: Background and Research Contextmentioning
confidence: 99%
“…Rice (2002, p. 558) apresenta, ainda, estudos que mostram que concepções imprecisas adquiridas durante a infância tendem a se manter na vida adulta. Perspectivas similares são assumidas e demonstradas por outros autores (ROYCE;WILEY, 1996;SACKES;TRUNDLE;FLEVARES, 2009). Por conta disso, Rice (2002) defende a precisão conceitual como critério para a seleção de livros comerciais em sala de aula e apresenta outros critérios, geralmente sugeridos por pesquisadores: personagens críveis, passagem do tempo realista, igualdade de raça e gênero, qualidade das ilustrações, distinção entre fatos e fantasia e informação atualizada (RICE, 2002, p. 560).…”
Section: Introductionunclassified